Perancangan UI/UX Prototipe Reservasi Kelas Olahraga Melalui Pendekatan Human Centered Design - Desma Noor Putri; Diena Noviarini; Ringga Sentagi Asa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid growth of the digital fitness application industry has encouraged the emergence of various sportstech platforms to meet public demand for flexible and practical access to sports services. However, existing sports class reservation platforms still face several issues related to user interface and user experience aspects, particularly unclear cancellation policies, limited rescheduling features, and lack of transparency regarding class availability information. This study aims to identify user needs and obstacles in the sports class booking process, as well as to design the Go-FIT website prototype as a user-oriented solution. The approach used in this study is Human-Centered Design (HCD), implemented through five stages of design thinking: empathize, define, ideate, prototype, and testing. Data were collected through pre-surveys, literature studies, and observation of user reviews on existing sports class reservation platforms. The prototype was developed using Figma and Loveable as an AI-assisted development platform. Evaluation was conducted with 30 respondents using the System Usability Scale (SUS) instrument. The test results showed an average SUS score of 82,5, which falls into the Excellent category, indicating that the Go-FIT prototype has a very high level of usability in terms of effectiveness, efficiency, and overall ease of use. The results of this study are expected to serve as a foundation for developing a more transparent, flexible, and user-oriented digital sports class reservation system.